97.9k views
3 votes
Follow the steps to solve this equation.

3(2x + 6) – 4x = 2(5x – 2) + 6

1. Use the distributive property: 6x + 18 – 4x = 10x – 4 + 6

2. Combine like terms: 2x + 18 = 10x + 2

3. Use the subtraction property of equality: 18 = 8x + 2

4. Use the subtraction property of equality: 16 = 8x

5. Use the division property of equality:


= x

2 Answers

3 votes

Answer: B or 2

Explanation:

User Ryan Gooler
by
4.7k points
3 votes

Answer:

2

Explanation:

User Shimon Rachlenko
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.